Tanggungjawab Perubatan dalam Pembedahan yang dibantu Robot Menurut Perspektif Etika Islam dan Fiqh: Medical Responsibility in Robot-Assisted Surgery from Islamic Ethical and Fiqh Perspectives - Yunos, Ahmad Safwan; Wan Saifuddin, Wan Muhammad Syahmi; Hamdan, Mohammad Naqib; Baharudin, Mohammad Hidir (Jurnal Fiqh, 2025)
The advancement of medical technology has introduced robot-assisted surgery, offering enhanced surgical precision and faster patient recovery. However, its application raises complex questions regarding medical responsibility from both Islamic ethical and fiqh perspectives. This paper explores the nature of medical liability in robot-assisted procedures by examining ethical, criminal, and contractual dimensions, while addressing the roles of surgeons, manufacturers, hospitals, and related parties. Employing a qualitative methodology, the study of classical fiqh sources, contemporary fatwas, and legal frameworks. The data was analyzed using a content analysis method which involved identifying through main themes such as responsibility, liability, taʿzīr and qiṣāṣ. It concludes that the application of responsibility in robot-assisted surgery provides a comprehensive and Shariah-accountability model to ensure justice, patient safety and trustworthiness.